PENERAPAN MESIN MIXER ADONAN BAKSO DAN SIOMAY (MEAT MINCER) UNTUK MENINGKATKAN PRODUKTIVITAS USAHA UMKM - Alfauzi, Abdul Syukur; Herlambang, Yusuf Dewantoro; Sahid, Sahid; Munawwaroh, Dita Anies (Politeknik Negeri Semarang, 2024)
The Meat Mincer serves to stir the meatball and siomay dough, so that the siomay and meatball dough is mixed and chopped into soft and smooth and evenly mixed. The material inserted in the mixer machine is meat that has been ground with a meat grinder. In addition to dumplings, this dough mixer machine is also for other similar products that require the process of chopping and mixing dough, for example meatballs, sausages, tempurah, and various other dishes, this model meatball dough mixer machine is made of full stainless steel anti-rust. This machine is equipped with an ice cube collection tube around the container (mixer tube), this is very useful for the production process. The lid of this meatball and dumpling mixer machine is equipped with a hole on top. This hole is useful for viewing the dough mixing process, and is also useful for pouring meatball and siomay spices. The home industry partner of the siomay business is located in Meteseh Village, Tembalang District, Semarang City.Machine implementation includes assembling and installing the machine at the partner location, as well as training on machine operation and maintenance. The final stage of the service is evaluation and mentoring. Evaluation is carried out by directly assessing the partners' operational practices on the machines that have been donated. Assistance includes supervision, work control, and direction when partners produce meatballs and dumplings using production machines. It is expected that the Meatball and Siomay Dough Mixer will be able to increase partner siomay production.